People, cities, and wealth the transformation of traditional society - Wrigley, E. A. (Edward Anthony) 1931- (Oxford Basil Blackwell, 1987)
Between the sixteenth and nineteenth centuries, England and Western Europe were transformed from rural, agricultural societies into urbanized, industrial ones, the average person changing from a peasant into a factory or office worker. This book describes and analyses the transformation: it considers the interrelations between population characteristics, urban growth and the creation of wealth, and explores the reasons why Western Europe has developed along lines so different from those of other major cultures.
Includes bibliographical references (pages 322-335) and index.
Keywords: Urban economics -- History; Cities and towns -- Europe -- Growth -- History; Fertility, Human -- Europe -- History; Europe -- Industry -- History